Interações, sentidos e riscos no atacado de moda do Bom Retiro, São Paulo: a diferenciação da Rua Aimorés - Zarpellon, Jaqueline Cavalcanti (2017)
This research aims at understanding the fashion wholesale trade of Bom Retiro, a neighborhood in the capital of São Paulo, having a corpus of the distinctive Rua Aimorés (Aimorés street), where brands and respective important stores in such segment are concentrated, accounting for 55% of Brazil’s women’s fashion. There is a question: to what extent do the values and positioning of this set of stores interact with their buyers – multibrand shopkeepers –, how do the interactions that build the meaning among stores, brands and buyers occur in the that texture, as well as what is the role of this particular commerce street in its characterization? And also, how do the multiple brands articulate their purchases among the options which the street disposes? The research analyzes how these consumption narratives are formed between the addresser – a cut of twelve stores in Rua Aimorés – donor of cognitive and performance skills (knowledge, power, acting) to the addressee – multibrand buyer from all over the country, and fashion becomes a value to be won by the buyer and susceptible to the positive sanction of its target audience. The interest in multi-brand stores is due to the great representation of this segment of fashion business throughout Brazil and the reference that such street takes – along with Professor Cesare Lombroso street – in a wholesale fashion pole. The theoretical basis used in this study is the semiotics of Algirdas Julien Greimas, with the methodological procedures of the meaning-generative path, and of the narrative grammar with the unfolding in regimes of meaning, risk and interaction that, implementing the logic of the junction with the logic of unity proposed by Eric Landowski, allow us to reach the dynamics of meaning. For the analysis of the plastic structure, we have invoked Jean-Marie Floch and Ana Claudia de Oliveira, especially in issues which concern fashion and configurations of city points and showcases. On the latter, we use the contributions of Sylvia Demetresco. We find the composition of a neighborhood sediment in fashion retailer practices and wholesalers. We observe the force of action of different immigrant flows, among which, at the moment, stands out the Koreans, in the construction of the ready-made fashion wholesale. We also understand how the gathering of trades that converge forces into their work corroborates the solidity of fashionable mercantile practices in the city of São Paulo. Amongst the results achieved, we highlight the development of a typology of wholesale stores based on values, whose systematization encompasses the characterization of multi-brand buyers and their target audience. This investigation fills a gap in studies on the wholesale trade in women’s fashion